A SAXS study of the nanostructural characteristics of TEOS-derived sonogels upon heat treatment up to 1100 degrees C - Vollet, D. R.; Donatti, D. A.; Ruiz, A. L. (Elsevier B.V., 2002)
Xerogels obtained from the acid-catalyzed and ultrasound stimulated hydrolysis of TEOS were submitted to heat treatment at temperatures ranging from 60 to 1100 degreesC and studied by small-angle X-ray scattering (SAXS). The SAXS intensity as a function of the modulus of the scattering vector q was obtained in the range from q(0) = 0.19 to q(m) = 4.4 nm(-1). At 60 degreesC the xerogels exhibit an apparent surface fractal structure with a fractal dimension D-s similar to 2.5 in a length scale ranging from 1/q(1) similar to 1 to 1/q(m) similar to 0.22 nm. This structure becomes extremely rough at 120 degreesC (D-s similar to 3) and at 150 degreesC, it apparently converts to a mass fractal with a fractal dimension D similar to 2.4. This may mean an emptying of the pores with preservation of a share of the original mass fractal structure of the wet aged gel, for it had presented a mass fractal dimension D similar to 2.2. A well characterized porous structure formed by 2.0 nm mean size pores with smooth surface of about 380 m(2)/g is formed at 300 degreesC and remains stable until approximately 800 degreesC. At 900 degreesC the SAXS intensity vanishes indicating the disappearance of the pores in the probed length scale. The elimination of the nanopores occurs by a mechanism in which the number of pores diminishes keeping constant their mean size. The xerogels exhibit a foaming phenomenon above 900 degreesC and scatter following Porod's law as does a surface formed by a coarse structure. (C) 2002 Elsevier B.V. B.V. All rights reserved.